Gabor Directional Binary Pattern: An Image Descriptor for Gaze Estimation. (29th August 2010) - Ge Ge, Hongzhi Hongzhi
Abstract : This paper proposes an image descriptor, Gabor Directional Binary Pattern (GDBP), for robust gaze estimation. In GDBP, Gabor magnitude information is extracted firstly from a cropped subimage. The local directional derivations are then utilized to encode the binary patterns in the given orientations. As an image descriptor, GDBP can suppress noises and robustness to illumination variations. Meanwhile, the encoding pattern can emphasize boundary. We use the GDBP features of eye regions and adopt the Support Vector Regression (SVR) to approximate the gaze mapping function, which is then used to predict the gaze direction with respect to the camera coordinate system. In the person-independent experiments, our dataset includes 4089 samples of 11 persons. Experimental results show that the gaze estimation can achieve an accuracy of less than 2 ∘ by using the proposed GDBP and SVR.